Comparative Effectiveness of Digital and Conventional Oscilloscopes in Resonance Tube Practicum - Susanti, Desi; Pramudya, Yudhiakto; Ishafit, Ishafit (Department of Physics Education, Universitas Mataram, 2025)
This study investigates the comparative effectiveness of digital and conventional oscilloscopes in physics learning, focusing on the resonance tube practicum as a medium for understanding acoustic wave phenomena. Digital tools such as the Soundcard Oscilloscope have been proposed as innovative and low-cost alternatives to conventional laboratory equipment, addressing resource limitations in many schools. A quantitative quasi-experimental nonequivalent control group design was employed involving two classes of eleventh-grade students. Learning outcomes were measured using validated pre-test and post-test instruments. Data were analyzed through descriptive statistics, Wilcoxon Signed Rank tests for within-group changes, and Mann–Whitney U tests for between-group comparisons due to non-normal data distribution. The experimental group demonstrated significant improvement in learning outcomes (p = 0.003), confirming the effectiveness of the digital tool, while the control group did not (p = 0.094). Although the Mann–Whitney test indicated no significant difference between groups (p = 0.873), N-Gain analysis revealed a notable contrast: a low gain (0.095) in the experimental group versus a decrease (–0.262) in the control group. This research offers novelty by directly comparing digital and conventional oscilloscopes in resonance tube experiments, highlighting the gap between statistical significance and pedagogical effectiveness. The findings demonstrate that the Soundcard Oscilloscope serves as a viable, low-cost alternative that yields greater learning gains than its conventional counterpart. These results underscore the potential of integrating affordable digital laboratory tools with active learning strategies to enhance conceptual understanding, particularly in resource-constrained educational contexts.